Correction: Lian et al. Microstructure and Mechanical Property of Mg-3Al-1Zn Magnesium Alloy Sheet Processed by Integrated High Temperature Rolling and Continuous Bending. Metals 2020, 10, 380 - Yong Lian; Benhong Liao; Tao Zhou; Wenjun Ge; Laixin Shi; Li Hu; Mingbo Yang; Jin Zhang (Metals)
In the original publication, there were mistakes in Figures 2d, 3, 4b, 5, 6d and 7b as published [...]